2013
DOI: 10.4081/audiores.2013.e4
|View full text |Cite
|
Sign up to set email alerts
|

Cervical and Ocular Vestibular Evoked Myogenic Potentials Test Results in Individuals with Auditory Neuropathy Spectrum Disorders

Abstract: Auditory neuropathy spectrum disorder is a clinical disorder where the outer hair cell functioning is intact but the functioning of the auditory nerve is affected. Since, the 8th nerve is constituted by both the auditory and vestibular branch of nerve fibers, there are chances that the vestibular nerve might also be affected. Hence, the current study was carried out in order to determine the functioning of vestibular nerve in individuals with auditory neuropathy. A total of 11 participants were considered for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Interestingly, the results of the study showed that In addition, ocular vestibular evoked myogenic potential are also affected and is suggestive of abnormal superior vestibular nerve functioning (8). The neuropathy may not be restricted only to the auditory branch or the vestibular branch of the eighth cranial nerve.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Interestingly, the results of the study showed that In addition, ocular vestibular evoked myogenic potential are also affected and is suggestive of abnormal superior vestibular nerve functioning (8). The neuropathy may not be restricted only to the auditory branch or the vestibular branch of the eighth cranial nerve.…”
Section: Resultsmentioning
confidence: 80%
“…Vertigo is also one of the symptoms reported by individuals with ANSD. These individuals also exhibit vestibular neuropathy along with auditory difficulties (6)(7)(8).The individuals with ANSD are also reported to have vestibular neuropathy along with auditory difficulties (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…105,106 A later study involving oVEMPs showed a similar pattern. 107 Because the patients had auditory neuropathy, it was assumed the site of the lesion was the vestibular nerve. A more recent study looked specifically at patients with Charcot-Marie-Tooth (CMT) disease, a hereditary polyneuropathy, with confirmed involvement of the peripheral nerves.…”
Section: Neuropathies Affecting the Vestibular Nervementioning
confidence: 99%